Polymer Thin Films for Anti‐Reflection and Passivation on the Front Surface of Interdigitated Back Contact c‐Si Solar Cell (Solar RRL 7∕2017). Issue 7 (July 2017) - Chen, Jianhui; Shen, Yanjiao; Chen, Bingbing; Ge, Kunpeng; Guo, Jianxin; Wang, Ziqian; Li, Feng; Xu, Ying; Mai, Yaohua
Abstract : Inorganic thin films, such as silicon nitride (SiNx ) and silicon oxide (SiOx ), play an important role in crystalline silicon (c‐Si) photovoltaic cells by acting as the anti‐reflection (AR) coating and surface passivation (SP) layers. However, the deposition of these inorganic films requires expensive high vacuum systems and rather high processing temperature, which counteracts the efforts in cost reduction of the developing PV industry. Here (article No.201700079 ), the authors show that a polymeric thin film, polystyrenesulfonate (PSS), deposited by a low cost, low temperature, vacuum‐free spin coating technique, yields superior surface passivation for c‐Si wafer, as compared to the conventional passivating materials, such as SiNx and SiOx . Owing to its suitable refractive index and high transparency, PSS can also be used as AR coating, which reduces the sunlight reflection loss in c‐Si solar cells. In this work, PSS thin film is applied for the first time to interdigitated back contact (IBC) silicon solar cells as AR and SP multi‐functional layer, leading to an average increase in power conversion efficiency by ̃10%.